Climate Change Education in Formal Settings, K-14: A Workshop Summary - National Research Council (The National Academies Press, 2012)
Climate change is occurring, is very likely caused by human activities, and poses significant risks for a broad range of human and natural systems. Each additional ton of greenhouse gases emitted commits us to further change and greater risks. In the judgment of the Committee on America's Climate Choices, the environmental, economic, and humanitarian risks of climate change indicate a pressing need for substantial action to limit the magnitude of climate change and to prepare to adapt to its impacts. A principal message from the recent National Research Council report, America's Climate Choices, this brief summary of how climate change will shape many aspects of life in the foreseeable future emphasizes the vital importance of preparation for these changes.
Keywords: Earth Sciences; Education

Communities, Climate Change, and Health Equity: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
As the effects of climate change become more widespread and significant, communities least able to respond are bearing the largest burden. In the United States, communities disadvantaged by a legacy of racial segregation and environmental injustice struggle with disparate health outcomes, are vulnerable to the effects of climate change (e.g., severe flooding in low-lying areas and extreme heat in urban neighborhoods), and lack sufficient resources to recover from and rebuild for resilience against future events. On October 12 and 14, 2021, the 2-day virtual workshop "Communities, Climate Change, and Health Equity - A New Vision" brought together environmental health experts, resilience practitioners, climate scientists, and people with lived experience to discuss the disproportionate impact of climate change on communities experiencing health disparities and environmental injustice. During the workshop, the first in a four-part series, 41 speakers shared their perspectives on the topic and suggested specific actions that decision-makers can take to address the intersecting crises of climate change and health inequity. This publication summarizes the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies

Incorporating Climate Change and Climate Policy into Macroeconomic Modeling: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Macroeconomic models, essential for decision making and federal budget planning, may not appropriately consider the wide breadth of climate-related impacts that potentially have large macroeconomic significance. Challenges integrating climate factors into macroeconomic analyses can stem from the complexity of macroeconomics, climate science, policy instruments, and their interactions. Although economists have made progress in developing tools to understand climate-related impacts on the macroeconomy, much of the climate and macroeconomic research has historically been conducted in disciplinary silos that can limit a holistic understanding of climate-related impacts on the macroeconomy. The National Academies of Sciences, Engineering, and Medicine, under the auspices of the Roundtable on Macroeconomics and Climate-Related Risks and Opportunities, convened a workshop on June 14-15, 2023, to consider current macroeconomic models and suggest opportunities that may improve the incorporation of climate-related factors into macroeconomic modeling. Through panels of invited speakers and an interactive breakout discussion, the workshop explored an array of macroeconomic models and potential pathways to integrate some of the physical and transition effects of climate change. This publication summarizes the presentations and discussion of the workshop.
Keywords: Environment and Environmental Studies; Industry and Labor

Climate Change Education: Goals, Audiences, and Strategies: A Workshop Summary - National Research Council (The National Academies Press, 2011)
The global scientific and policy community now unequivocally accepts that human activities cause global climate change. Although information on climate change is readily available, the nation still seems unprepared or unwilling to respond effectively to climate change, due partly to a general lack of public understanding of climate change issues and opportunities for effective responses. The reality of global climate change lends increasing urgency to the need for effective education on earth system science, as well as on the human and behavioral dimensions of climate change, from broad societal action to smart energy choices at the household level.
Keywords: Education; Environment and Environmental Studies; Earth Sciences

Communities, Climate Change, and Health Equity: Lessons Learned in Addressing Inequities in Heat-Related Climate Change Impacts: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Extreme heat is a pervasive and critical hazard of climate change. While heat poses a significant threat to large swaths of the human population, it is not affecting all people or all communities equally. To explore what it takes to prevent and mitigate inequitable health impacts from extreme heat, the National Academies Environmental Health Matters Initiative (EHMI) organized a workshop on June 20-21, 2023, titled Communities, Climate Change, and Health Equity: Lessons Learned in Addressing Inequities in Heat-Related Climate Change Impacts. The workshop was the third in a series of EHMI events exploring the state of knowledge about climate-related health disparities. This hybrid event convened people with lived experience in communities affected by extreme heat; experts in environmental health, economic, and racial justice; climate scientists; energy specialists; and people involved in sustainable planning and disaster relief. Through presentations, shared stories, and interactive discussions, participants explored real-world challenges related to extreme heat, along with actions being pursued to prevent, adapt to, or mitigate the health consequences.
Keywords: Environment and Environmental Studies; Health and Medicine

Communities, Climate Change, and Health Equity—State-Level Implementation: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Because of historic and ongoing discriminatory policies and practices, certain populations - namely people of color, Indigenous people, and low-income communities - disproportionately suffer from the adverse impacts of extreme weather and other disasters that are exacerbated by climate change. To examine actions that could help improve climate-related health outcomes in disproportionately impacted communities, the Environmental Health Matters Initiative, a program spanning all major units of the National Academies of Sciences, Engineering, and Medicine, convened a two-day workshop Communities, Climate Change, and Health Equity - State-Level Implementation on May 24 and 26, 2022. The workshop brought together representatives from state and federal agencies, universities, community-based organizations, state and national advocacy organizations, foundations, and private sector organizations. This publication highlights the presentations and discussion of the workshop.
Keywords: Environment and Environmental Studies

Climate Change Education: Engaging Family Private Forest Owners on Issues Related to Climate Change: A Workshop Summary - National Research Council (The National Academies Press, 2014)
The forested land in the United States is an asset that is owned and managed not only by federal, state, and local governments, but also by families and other private groups, including timber investment management organizations and real estate investment trusts. The more than 10 million family forestland owners manage the largest percentage of forestland acreage (35 percent) and the majority of the privately owned forestland (62 percent). The Forest Service of the United States Department of Agriculture, which is responsible for the stewardship of all of the nation's forests, has long worked with private owners of forestland on forest management and preservation. At a time when all forestland is facing intensified threats because of the long-term effects of global climate change, the Forest Service recognizes that family forestland owners play a key role in protecting forestland. It is working to identify optimal ways to engage this diverse group and support them in mitigating threats to the biologically diverse land they own or manage. Climate Change Education: Engaging Family Private Forest Owners on Issues Related to Climate Change is the summary of a workshop, convened by the National Research Council's Board on Science Education and Board on Environmental Change and Society as part of its Climate Change Education Roundtable series, to explore approaches to the challenges that face state foresters, extension agents, private forestry consultants, and others involved with private family forestland owners on how to take climate change into consideration when making decisions about their forests. The workshop focused on how findings from the behavioral, social, and educational sciences can be used to help prepare for the impacts of climate change. The workshop participants discussed the threats to forests posed by climate change and human actions; private forestland owners' values, knowledge, and dispositions about forest management, climate change, and related threats; and strategies for improving communication between forestland owners and service providers about forest management in the face of climate change.
Keywords: Environment and Environmental Studies; Education; Earth Sciences

Climate Change Education: Preparing Future and Current Business Leaders: A Workshop Summary - National Research Council (The National Academies Press, 2014)
Climate change poses challenges as well as opportunities for businesses and, broadly speaking for the entire economy. Businesses will be challenged to provide services or products with less harmful influence on the climate; respond to a changing policy, regulatory, and market environment; and provide new services and products to help address the challenges of a changing climate. Many businesses are beginning to see climate change as another context within which they need to consider their core functions of strategy, finance, operations, marketing, and their regulatory environments, a context that poses both risks and opportunities. Climate Change Education: Preparing Current and Future Business Leaders is the summary of a workshop hosted by the National Research Council's Board on Science Education in March 2013 to explore issues associated with teaching climate change-related topics in business schools. The workshop focused on major gaps in understanding of climate and sustainability education in postsecondary professional schools of business. The workshop also connected the topic of climate education for current and future business leaders with a broader discussion on climate change education and how they influence and can benefit each other. This report discusses the role that business schools could play in preparing future corporate leaders for the challenges and opportunities that climate change poses.
Keywords: Environment and Environmental Studies; Education; Earth Sciences

COVID-19 and the K-12 Teacher Workforce: Seizing the Moment to Reimagine Education: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
On June 1 and 2, 2021, the National Academies of Sciences, Engineering, and Medicine held a virtual workshop, Teaching and the Teaching Workforce Amid the Struggles of COVID-19 and for Racial Justice. The workshop was designed to revisit findings from the 2020 National Academies' report Changing Expectations for the K-12 Teacher Workforce: Policies, Preservice Education, Professional Development, and the Workplace, in the context of the COVID-19 pandemic. Experts from the original study committee, as well other leading scholars on the teacher workforce, explored how the COVID-19 pandemic has changed (or not changed), what teachers need, and where the teacher workforce is vulnerable. This publication highlights the presentation and discussion of the workshop.
Keywords: Education

Modeling the Health Risks of Climate Change: Workshop Summary - National Research Council (The National Academies Press, 2015)
Climate change poses risks to human health and well-being through shifting weather patterns, increases in frequency and intensity of heat waves and other extreme weather events, rising sea levels, ocean acidification, and other environmental effects. Those risks occur against a backdrop of changing socioeconomic conditions, medical technology, population demographics, environmental conditions, and other factors that are important in determining health. Models of health risks that reflect how health determinants and climate changes vary in time and space are needed so that we can inform adaptation efforts and reduce or prevent adverse health effects. Robust health risk models could also help to inform national and international discussions about climate policies and the economic consequences of action and inaction. Interest in resolving some of the challenges facing health effects modelers and health scientists led the National Research Council's Standing Committee on Emerging Science for Environmental Health Decisions to hold a workshop on November 3-4, 2014, in Washington, DC, to explore new approaches to modeling the human health risks of climate change. Throughout the workshop, the discussions highlighted examples of current application of models, research gaps, lessons learned, and potential next steps to improve modeling of health risks associated with climate change. Modeling the Health Risks of Climate Change summarizes the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies

The Nexus of Biofuels, Climate Change, and Human Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Liquid fuels are a major part of modern life. They supply energy for ground, water, and air transportation as well as power for industrial and farming machinery. But fossil fuels - the dominant liquid fuel in use for well over a century - have many disadvantages. The use of fossil fuels has obvious health downsides, such as emissions of pollutants that are directly harmful to health. The burning of fossil fuels produces greenhouse gases, which contribute to global warming, itself a long-term threat to human health. There have also been health concerns related to insecurity of liquid fuel supplies and the potential of international conflicts being caused by fuel scarcity. Furthermore, there are concerns that the world's large but still limited supply of fossil fuels could be strained by the increasing demand that results from societies around the world achieving greater prosperity. In the face of these concerns, new policies have been created that encourage the development of renewable sources of energy in general and biofuels in particular. In January 2013, the Roundtable on Environmental Health Sciences, Research, and Medicine of the Institute of Medicine held a 2- day, interactive, public workshop on the intersection of biofuels, climate change, and human health. Workshop attendees explored public health issues related to the composition of traditional and alternative fuels and fuel additives, and they discussed the known and potential health impacts associated with the use of these fuels and fuel additives. The Nexus of Biofuels, Climate Change, and Human Health is the summary of that workshop. This report examines air, water, land use, food, and social impacts of biomass feedstock as an energy resource, and the state of the science and health policy implications of using different types (and generations) of biofuels as an energy source.
Keywords: Health and Medicine

Engineering Responses to Climate Change: Proceedings of a Forum - National Academy of Engineering (The National Academies Press, 2022)
At the forum held during the 2021 annual meeting of the National Academy of Engineering, distinguished engineers gathered virtually to explore the roles that engineers can play in both mitigating and helping society adapt to climate change. Through a series of brief presentations and responses to questions from the moderator and the forum audience, the speakers discussed many of the issues at the forefront of climate-related engineering practice and policy today. This publication highlights the presentation and discussion of the event.
Keywords: Engineering and Technology; Environment and Environmental Studies

Including Health in Global Frameworks for Development, Wealth, and Climate Change: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Including Health in Global Frameworks for Development, Wealth, and Climate Change is the summary of a three-part public webinar convened by the Institute of Medicine Roundtable on Environmental Health Sciences, Research, and Medicine and its collaborative on Global Environmental Health and Sustainable Development. Presenters and participants discussed the role of health in measuring a country's wealth (going beyond gross domestic product), health scenario communication, and international health goals and indicators. The workshop focused on fostering discussion across academic, government, business, and civil society sectors to make use of existing data and information that can be adapted to track progress of global sustainable development and human health. This report examines frameworks for global development goals and connections to health indicators, the role for health in the context of novel sustainable economic frameworks that go beyond gross domestic product, and scenarios to project climate change impacts.
Keywords: Health and Medicine

Nutrition Education in the K-12 Curriculum: The Role of National Standards: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The childhood obesity epidemic and related health consequences are urgent public health problems. Approximately one-third of America's young people are overweight or obese. Health problems once seen overwhelmingly in adults, such as type 2 diabetes, cardiovascular disease, and hypertension, are increasingly appearing in youth. Though the health of Americans has improved in many broad areas for decades, increases in obesity could erode these and future improvements. The IOM report Accelerating Progress in Obesity Prevention: Solving the Weight of the Nation recognized the importance of the school environment in addressing the epidemic and recommended making schools a focal point for obesity prevention. The development and implementation of K-12 nutrition benchmarks, guides, or standards (for a discussion of these terms, see the next section of this chapter) would constitute a critical step in achieving this recommendation. National nutrition education curriculum standards could have a variety of benefits, including the following:
Keywords: Food and Nutrition

Engaging Socially Vulnerable Communities and Communicating About Climate Change–Related Risks and Hazards - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Extreme weather events exacerbated by climate change can compound existing vulnerabilities and inequities experienced by socially vulnerable people including pregnant people, children, low-income populations, Indigenous populations, immigrant groups, the elderly, people with disabilities, vulnerable occupation groups, communities of color, and people with preexisting or chronic medical conditions. Decision makers need to adopt strategies for engaging these communities on an ongoing basis to inform and empower individual decision making, identify and understand local concerns, and provide the necessary resources. This rapid expert consultation highlights how decision makers can continuously engage with vulnerable communities, as well as communicate risk and promote adaptation in the face of extreme weather events exacerbated by climate change. Implementing this guidance can help decision makers, researchers, and communities work collaboratively, linking analysis, deliberation, and program design to best adapt to climate change-related hazards and risks.
Keywords: Environment and Environmental Studies

Climate Change: Evidence and Causes: Update 2020 (The National Academies Press, 2020)
Climate change is one of the defining issues of our time. It is now more certain than ever, based on many lines of evidence, that humans are changing Earth's climate. The Royal Society and the US National Academy of Sciences, with their similar missions to promote the use of science to benefit society and to inform critical policy debates, produced the original Climate Change: Evidence and Causes in 2014. It was written and reviewed by a UK-US team of leading climate scientists. This new edition, prepared by the same author team, has been updated with the most recent climate data and scientific analyses, all of which reinforce our understanding of human-caused climate change. Scientific information is a vital component for society to make informed decisions about how to reduce the magnitude of climate change and how to adapt to its impacts. This booklet serves as a key reference document for decision makers, policy makers, educators, and others seeking authoritative answers about the current state of climate-change science.
Keywords: Environment and Environmental Studies

The Roles of Trust and Health Literacy in Achieving Health Equity: Clinical Settings: Proceedings of a Workshop-in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Roundtable on Health Literacy convened the first of three workshops to explore the positive impacts on health equity improved literacy practices in clinical settings can have. To relate and inspire confidence, physicians must communicate plainly and at the literacy level of the patient and recognize the knowledge the patient brings. Equality and equity are not the same, and treating every patient, their conditions, history, and identity, identically can interfere with trust. Diversifying the work force can facilitate better clinical practices that honor all patients. This Proceedings document summarizes workshop discussions.
Keywords: Health and Medicine

The Roles of Trust and Health Literacy in Achieving Health Equity: Community Settings: Proceedings of a Workshop-in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Roundtable on Health Literacy convened the third of three workshops to address the themes of trust and positive health equity outcomes that arise from strategic community-based organization practices. Given the historical and current reasons individuals and communities with marginalized identities have to mistrust public health communications and institutions, health literacy is essential. To bolster mutual trust, hospitals, payers, providers, and public health professionals should have the cultural competence and humility to match the health literacy needed from their patients.This Proceedings document summarizes workshop discussions.
Keywords: Health and Medicine

An Update on Research Issues in the Assessment of Birth Settings: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2013)
More than 30 years ago, the Institute of Medicine (IOM) and the National Research Council (NRC) convened a committee to determine methodologies and research needed to evaluate childbirth settings in the United States. The committee members reported their findings and recommendations in a consensus report, Research Issues in the Assessment of Birth Settings (IOM and NRC, 1982). An Update on Research Issues in the Assessment of Birth Settings is the summary of a workshop convened in March, 2013, to review updates to the 1982 report. Health care providers, researchers, government officials, and other experts from midwifery, nursing, obstetric medicine, neonatal medicine, public health, social science, and related fields presented and discussed research findings that advance our understanding of the effects of maternal care services in different birth settings on labor, clinical and other birth procedures, and birth outcomes. These settings include conventional hospital labor and delivery wards, birth centers, and home births. This report identifies datasets and relevant research literature that may inform a future ad hoc consensus study to address these concerns.
Keywords: Health and Medicine

Climate Security in Central America: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
To advance a systems understanding of climate-related security risks in the Central America region, the National Academies of Sciences, Engineering, and Medicine convened a workshop titled Climate Security in Central America on May 3-4, 2023. The workshop was held under the auspices of the National Academies Climate Security Roundtable. Over two days, workshop participants considered some of the underlying environmental, social, economic, and political dynamics at play in Central America; they explored indicators and pathways for climate-related security risks in the region; and they considered the available tools for analyzing and forecasting these risks. This publication summarizes the presentations and discussion of the workshop.
Keywords: Environment and Environmental Studies; Conflict and Security Issues